Tumor-derived exosomes: Nanovesicles made by cancer cells to promote cancer metastasis - Hongwei Chen; Venkata Chengalvala; Hongxiang Hu; Duxin Sun (Elsevier, 2021)
Nanomedicine usually refers to nanoparticles that deliver the functional drugs and siRNAs to treat cancer. Recent research has suggested that cancer cells can also make nanoparticles that also deliver functional molecules in promoting cancer metastasis, which is the leading cause of various cancer mortalities. This nanoparticle is called tumor-derived vesicles, or better-known as tumor-derived exosomes (TEXs). TEXs are nanoscale membrane vesicles (30-140 nm) that are released continuously by various types of cancer cells and contain tumor-derived functional biomolecules, including lipids, proteins, and genetic molecules. These endogenous TEXs can interact with host immune cells and epithelial cells locally and systemically. More importantly, they can reprogram the recipient cells in favor of promoting metastasis through facilitating tumor cell local invasion, intravasation, immune evasion, extravasation, and survival and growth in distant organs. Growing evidence suggests that TEXs play a key role in cancer metastasis. Here, we will review the most recent findings of how cancer cells harness TEXs to promote cancer metastasis through modulating vascular permeability, suppressing systemic immune surveillance, and creating metastatic niches. We will also summarize recent research in targeting TEXs to treat cancer metastasis.